The Effect of Work Flexibility on Employee Well-being and Organizational Commitment - Amelia Amelia (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
Work flexibility has become an increasingly important element of modern human resource management, particularly in response to rapid technological change and shifting workforce expectations. Flexible work arrangements, including schedule, location, and task flexibility, are believed to influence important employee outcomes such as well-being and organizational commitment. However, empirical evidence regarding these relationships in emerging economies such as Indonesia remains limited. This study aims to examine the effect of work flexibility on employee well-being and organizational commitment, as well as to explore the mediating role of employee well-being in the relationship between work flexibility and organizational commitment. A quantitative approach with a descriptive–verification design was employed. Data were collected from 378 private sector employees in Bandung, Indonesia, using a structured questionnaire distributed both online and offline. The measurement instruments included the Work Flexibility Scale, the Warwick-Edinburgh Mental Well-being Scale (WEMWBS), and the Three-Component Model of Organizational Commitment. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 24.0. The results indicate that work flexibility has a significant positive effect on employee well-being (? = 0.541, p < 0.001) and organizational commitment (? = 0.312, p < 0.001). Employee well-being also significantly influences organizational commitment (? = 0.489, p < 0.001) and partially mediates the relationship between work flexibility and organizational commitment. These findings highlight the strategic importance of implementing flexible work arrangements to enhance employee well-being and strengthen organizational commitment in Indonesian organizations.